Localization and role of inward rectifier K+ channels in Malpighian tubules of the yellow fever mosquito Aedes aegypti. (December 2015) - Piermarini, Peter M.; Dunemann, Sonja M.; Rouhier, Matthew F.; Calkins, Travis L.; Raphemot, Rene; Denton, Jerod S.; Hine, Rebecca M.; Beyenbach, Klaus W.
Abstract: Malpighian tubules of adult female yellow fever mosquitoes Aedes aegypti express three inward rectifier K + (Kir) channel subunits: Ae Kir1, Ae Kir2B and Ae Kir3. Here we 1) elucidate the cellular and membrane localization of these three channels in the Malpighian tubules, and 2) characterize the effects of small molecule inhibitors of Ae Kir1 and Ae Kir2B channels (VU compounds) on the transepithelial secretion of fluid and electrolytes and the electrophysiology of isolated Malpighian tubules. Using subunit-specific antibodies, we found that Ae Kir1 and Ae Kir2B localize exclusively to the basolateral membranes of stellate cells and principal cells, respectively; Ae Kir3 localizes within intracellular compartments of both principal and stellate cells. In isolated tubules bathed in a Ringer solution containing 34 mM K +, the peritubular application of VU590 (10 μM), a selective inhibitor of Ae Kir1, inhibited transepithelial fluid secretion 120 min later. The inhibition brings rates of transepithelial KCl and fluid secretion to 54% of the control without a change in transepithelial NaCl secretion. VU590 had no effect on the basolateral membrane voltage (Vbl ) of principal cells, but it significantly reduced the cell input conductance (gin ) to values 63% of the control within ∼90 min. In contrast, the peritubular application of VU625 (10 μM), an inhibitor of both Ae Kir1 and Ae Kir2B, started to inhibit transepithelial fluid secretion as early as 60 min later. At 120 min after treatment, VU625 was more efficacious than VU590, inhibiting transepithelial KCl and fluid secretion to ∼35% of the control without a change in transepithelial NaCl secretion. Moreover, VU625 caused the Vbl and gin of principal cells to respectively drop to values 62% and 56% of the control values within only ∼30 min. Comparing the effects of VU590 with those of VU625 allowed us to estimate that Ae Kir1 and Ae Kir2B respectively contribute to 46% and 20% of the transepithelial K + secretion when the tubules are bathed in a Ringer solution containing 34 mM K + . Thus, we uncover an important role of Ae Kir1 and stellate cells in transepithelial K + transport under conditions of peritubular K + challenge. The physiological role of Ae Kir3 in intracellular membranes of both stellate and principal cells remains to be determined. Graphical abstract: Highlights: Ae Kir1 and Ae Kir2B channels localize to the basolateral membranes of stellate and principal cells, respectively. Ae Kir3 channels localize to intracellular compartments of principal and stellate cells. Ae Kir1 channels contribute to 46% of the transepithelial K + secretion in tubules challenged to secrete K + at high rates. Ae Kir2B channels contribute to 20% of the transepithelial K + secretion in tubules challenged to secrete K + at high rates. The role of intracellular Ae Kir3 channels in transepithelial K + secretion remains to be elucidated.